Turkish-English subtitling strategies in Turkey :|the case of the 2014 Istanbul film festival - Baturay, Müzeyyen. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This thesis deals with the strategies adopted by the translators who provide English language subtitles for Turkish movies at the Istanbul Film Festival. The target audience of the English subtitles consists of both people within the sector (directors, festival organizers etc.) and foreign people living in or visiting Turkey. This non homogenous target audience makes the translation decision process more difficult. The study analyses 21 Turkish films translated by two Festival translators, a corpus which varies in terms of genre, content, and language use. It looks at the translators’ treatment of certain translation crisis points and of longer samples. This translation analysis is supplemented by the findings from questionnaires answered by the translators and interviews with the ex- and current subtitle coordinator and translators of the film festival. This exploratory research presents data on the Festival and on translation practices there, which have not been dealt with systematically before. The translation strategies are explained and categorized with the help of Pedersen’s taxonomy of strategies and his notion of parameters (2005). The results are interpreted in terms of translational norms and the binary opposition between foreignization and domestication. It emerges that the translators opt for both source- (foreignization) and target-oriented (domestication) strategies. Translators seek more pragmatic solutions due to the particular requirements of subtitling. Translation decisions can be said to reflect a combination of norms and idiosyncrasies. The tendency towards domestication (target-oriented decisions) is more dominant, which makes the subtitles more fluent and easier for the target audience to follow.
Keywords: Turkish films -- Translation into English.; Turkish -- Language -- Translating into English.